Materialism and Tourism Brand Attachment in Influencing Compulsive Buying for Generations Y And Z Travel in the Post-Covid 19 Pandemic Period - Sudiyanti, Sudiyanti; Praharjo, Ardik; Parwati, Kardina Yudha; Alam, Aminullah (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the effect of materialism and tourism brand attachment on compulsive buying behavior for travel among Generations Y and Z in Indonesia during the post-COVID-19 period. It also explores the influence of destination image, perceived value, and ideal self-congruence on compulsive buying through materialism and brand attachment. A quantitative approach was employed, with data collected from 250 respondents and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM). The results reveal that materialism has a significant effect on compulsive buying behavior, and tourism brand attachment further amplifies this relationship. Additionally, destination image and perceived value are found to reinforce materialistic tendencies, which subsequently drive impulsive travel-related purchases. These findings offer valuable insights for tourism marketers targeting younger travelers by focusing on emotional attachment and materialistic appeals to encourage travel decisions.